MAXIMUM AIR SUCTION INTO HORIZONTAL OPEN ENDED CYLINDRICAL LOUVERED PIPE - SAMEER RANJAN SAHU; DIPTI PRASAD MISHRA (Journal of Engineering Science and Technology, 2017)
The main approach behind the present numerical investigation is to estimate the mass flow rate of air sucked into a horizontal open-ended louvered pipe from the surrounding atmosphere. The present numerical investigation has been performed by solving the conservation equations for mass, momentum and energy along with two equation based k-ɛ model for a louvered horizontal cylindrical pipe by finite volume method. It has been found from the numerical investigation that mass suction rate of air into the pipe increases with increase in louvered opening area and the number of nozzles used. Keeping other parameters fixed, for a given mass flow rate there exists an optimum protrusion of nozzle for highest mass suction into the pipe. It was also found from the numerical investigation that increasing the pipe diameter the suction mass flow rate of air was increased.